The Level of Knowledge as a Predictor of Husband’s Participation in Vasectomy: A Study at Buleleng I Community Health Center, 2023 - Armayanti, Luh Yenny; Mentari, Ketut Sri; Pratama Karma, Putu Rama (Fakultas Kedokteran Universitas Sriwijaya, 2025)
Male participation in Family Planning (FP) programs, particularly in permanent contraceptive methods such as vasectomy, remains significantly low in Indonesia. This study aimed to examine the relationship between the level of husband’s knowledge and their participation in vasectomy use within the working area of Buleleng I Public Health Center in 2023. Purposive sampling was used to choose 76 male respondents of reproductive age who were already parents in a cross-sectional, quantitative analytical study. A systematic questionnaire addressing two main variables knowledge of vasectomy and involvement in its use was used to gather data. Both univariate and bivariate techniques were used to analyze the data, and Pearson's correlation test was used to look at how the variables related to one another. A mean score of 80.80 (SD ±10.05) indicated that respondents had a high level of knowledge, whereas a mean score of 4.63 (SD ±0.72) indicated moderate participation in the vasectomy program. Knowledge and participation were shown to be significantly correlated by the correlation analysis (p = 0.001). These findings suggest that a husband's propensity to use vasectomy as a form of contraception increases with his degree of understanding. This study comes to the conclusion that one of the main factors influencing men's participation in vasectomy is knowledge. Therefore, community-based educational interventions and health promotion initiatives should be strengthened to enhance men’s awareness and involvement in family planning programs, as part of broader efforts to promote gender equity in reproductive health.